ZJU index as a predictive biomarker of gestational diabetes mellitus: a prospective cohort analysis - Xu, Ziyi; Li, Xuewei; Wang, Hui; Xu, Liuyang; Li, Changhui (Frontiers in Nutrition, 2025)
BackgroundThe ZJU index, incorporating fasting plasma glucose (FPG), lipid profiles, liver enzymes, and body mass index (BMI), serves as a multidimensional tool for assessing metabolic dysregulation. This prospective investigation examined first-trimester ZJU index associations with both gestational diabetes mellitus (GDM) risk and nonalcoholic fatty liver disease (NAFLD) during pregnancy, while simultaneously evaluating the relationships between lipid profiles, liver enzymes, and GDM development.MethodsWe conducted analyses using multivariable logistic regression and restricted cubic splines (RCS) to assess associations of the ZJU index, liver enzymes, and blood lipids with GDM, as well as the association between the ZJU index and NAFLD. Subgroup analyses were conducted to evaluate the correlation between the ZJU index (stratified by age and reproductive history) and GDM. The receiver operating characteristic (ROC) curve assessed the ZJU index’s predictive power. The robustness of the findings was verified via sensitivity analyses.ResultsIn the multivariable regression model, the ZJU index showed a significant positive association with GDM, after adjusting for confounders [OR = 1.22, 95% CI (1.13–1.32)]. The RCS analysis revealed a linear dose-response relationship between the ZJU index and GDM. The area under the curve (AUC) for the ZJU index was 0.802, indicating a high predictive ability for GDM. Associations between the ZJU index and GDM remained consistent across subgroups and sensitivity analyses.ConclusionThe ZJU index is closely associated with GDM prevalence.